PENERAPAN MODUL PENCEGAHAN KEKERASAN FISIK PADA ANAK USIA DINI : Penerapan Modul Pencegahan Kekerasan Fisik Pada Anak Usia Dini - Suryati; Welensi, Harteti (Ruang Ide Publisher, 2024)
Children who experience violence throughout their life will affect the process of growth and Children who experience violence throughout their lives will have an impact on their physical, psychological, social and behavioral growth and development processes. Acts of violence can cause children to lose the most basic things in their lives and result in death. Mothers are the main place for children's education, but mothers sometimes make the mistake of thinking that harsh education with physical punishment is a form of disciplining children. Efforts can be made to increase awareness and reduce the number of incidents of physical violence by providing information. Modules are one of the media which are teaching materials in printed form that are used for independent learning because in the modules there are learning instructions that individuals can study themselves. The aim of this research is to determine the influence of the physical violence prevention module in early childhood on mothers' knowledge about physical violence at the ABA Janturan Kindergarten, Yogyakarta. The research method used is experimental quantitative research using a pre-experimental design (one group pre-posttest design). The number of respondents was 60 mothers, the sampling technique used was total sampling. The instrument uses a module to prevent physical violence in early childhood and a knowledge questionnaire. Research analysis using the Paired t-test shows that there is a significant difference between the pre-test and post-test in maternal knowledge with a p-value of 0.000. The Prevention of Physical Violence in Early Childhood Module has a significant effect on mothers' knowledge. This module can be used as a guide in preventing physical violence, especially in early childhood